An Analysis of the Internationalization of the Animation Business Based on the Behavioral Intention of Millennial Users - Dunakhe, Chittranjan (Digital Repository of Theses, 2024)
The globalisation of the animation business and its attractiveness to millennial consumers have made it important hubs for the creative economy. This research looks at how internationalisation initiatives and the use patterns of millennials have shaped the animation business. Based on the Unified Theory of Acceptance and Use of Technology (UTAUT) 1, The UTAUT the study intends to examine how millennial users' behavioural intentions towards internationalised animated content are affected by a number of factors, such as social influence, performance expectancy, and enabling conditions. Methodologically, information on millennial consumers' attitudes and actions about internationalised animation was gathered using a quantitative survey. The framework is created via a thorough literature study, and then theories are developed using the UTAUT model. In order to empirically validate the study's findings, data analysis involves analysing the complex interactions between technology utilisation, user behaviour, and internationalisation. Findings indicate that millennial users intents to interact with internationalised animation are highly influenced by characteristics including perceived value, usefulness, and social impact. User involvement is also impacted by external issues like supply chain interruptions and piracy. Although the research provides useful suggestions for stakeholders in the animation business to improve strategic decision-making and user engagement, it also recognises several limitations, including sample size restrictions and self-reported data. To further our knowledge of user behaviour and technology adoption in animation, future study areas include analysing the effect of developing technologies on the animation business, evaluating the role of cultural variations on user behaviour, and examining a variety of viewpoints. All things considered, this research advances both theory and real-world applications in the animation industry's quest for worldwide growth.